Biodiversidad marina de Costa Rica: Filo Cnidaria - Cortés, Jorge (Revista de Biología Tropical, 1996)
This papero on the currenl knowledge of the marine biodiversity of Costa Rica. covers the Phylurn Cnidaria. A totlal of 2 1 5 species are reponed for Costa Rica. Four of these species are endemic 10 Cocos Island. The Class Hydrozoa is rcpresenled by 69 spccies in 49 genera 30 families and eight orders.